(untitled) (Clinics, 2012)
Temozolomide is an alkylating agent used in the treatment of gliomas and, more recently, aggressive pituitary adenomas and carcinomas. Temozolomide methylates DNA and, thereby, has antitumor effects. O6-methylguanine-DNA methyltransferase, a DNA repair enzyme, removes the alkylating adducts that are induced by temozolomide, thereby counteracting its effects. A Medline search for all of the available publications regarding the use of temozolomide for the treatment of pituitary tumors was performed. To date, 46 cases of adenohypophysial tumors that were treated with temozolomide, including 30 adenomas and 16 carcinomas, have been reported. Eighteen of the 30 (60%) adenomas and 11 of the 16 (69%) carcinomas responded favorably to treatment. One patient with multiple endocrine neoplasia type 1 and an aggressive prolactin-producing adenoma was also treated and demonstrated a good response. No significant complications have been attributed to temozolomide therapy. Thus, temozolomide is an effective treatment for the majority of aggressive adenomas and carcinomas. Evidence indicates that there is an inverse correlation between levels of O6-methylguanine-DNA methyltransferase immunoexpression and therapeutic response. Alternatively, high-level O6-methylguanine-DNA methyltransferase immunoexpression correlates with an unfavorable response. Here, we review the use of temozolomide for treating pituitary neoplasms.